Analytical Hierarchy Process Providing Loans to the North Sumatra Regional Police Cooperative Using the Analytical Hierarchy Process - Rizaldy Khair (Bahasa Indonesia, 2019)
Loans for civil servants and police employees must be given to employees who are entitled to receive them. Lending without any criteria makes other employees not accept them. Lending using criteria ensures that the employee given the loan is an employee who deserves to receive it. The ahp method is able to complete the selection of employees who are eligible for the loan. Because of the criteria that can determine the weight value for each attribute, and then proceed with a ranking process that will select the best alternative from a number of alternatives. In this case, the alternative in question is the one who is entitled to receive a loan based on attributes, or determining criteria in selecting employees who are eligible to receive loans. Based on the ranking, Juliana Situmorang's employee has the highest score of 0.977 compared to other employees. The ahp method is the right step in determining employees who are eligible to receive loans.